Deep sequencing of the prothoracic gland transcriptome reveals new players in insect ecdysteroidogenesis. - Nakaoka, T.; Iga, M.; Yamada, T.; Koujima, I.; Takeshima, M.; Zhou, X.; Suzuki, Y.; Ogihara, M.H.; Kataoka, H. (PLoS ONE, 2017)
Ecdysteroids are steroid hormones that induce molting and determine developmental timing in arthropods. In insect larva, the prothoracic gland (PG) is a major organ for ecdysone synthesis and release. Released ecdysone is converted into the active form, 20-hydroxyecdysone (20E) in the peripheral tissues. All processes from ecdysone synthesis and release from the PG to its conversion to 20E are called ecdysteroidogenesis and are under the regulation of numerous factors expressed in the PG and peripheral tissues. Classical genetic approaches and recent transcriptomic screening in the PG identified several genes responsible for ecdysone synthesis and release, whereas the regulatory mechanism remains largely unknown. We analyzed RNA-seq data of the silkworm Bombyx mori PG and employed the fruit fly Drosophila melanogaster GAL4/UAS binary RNAi system to comprehensively screen for genes involved in ecdysone synthesis and/or release. We found that the genes encoding ?-aminolevulinic acid synthase (CG3017/alas) and putative NAD kinase (CG33156) were highly expressed in the PG of both B. mori and D. melanogaster. Neither alas nor CG33156 RNAi-induced larvae could enter into the pupal stage, and they had a lower abundance of the active form ecdysteroids in their prolonged larval stage. These results demonstrated that alas and CG33156 are indispensable for ecdysteroidogenesis.